2006
DOI: 10.1016/j.adolescence.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Sexual sensation seeking and its relationship to risky sexual behaviour among African‐American adolescent females

Abstract: The relationship between sexual sensation seeking and sexual risk taking has been investigated among adult populations. There are limited data, however, regarding this relationship for adolescents. Since African-American adolescent females continue to be disproportionately diagnosed with STDs, including HIV, we examined this association among a clinic-based sample of African-American adolescent females (N ¼ 715) enrolled in an STD/HIV prevention intervention. Participants (ages 15-21) endorsing higher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
52
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 18 publications
9
52
1
4
Order By: Relevance
“…In addition, prior studies have included mixed samples and usually did not control for ethnic differences. Unfortunately, fewer studies have examined the relationship between SSS and risky sex among heterosexual youth and especially among those who are female (Gullette & Lyons, 2005;Spitalnick et al, 2007). More importantly, there is a dearth of studies which have examined the relationship between SSS and risky sex using prospective data (Kalichman et al, 1994(Kalichman et al, , 1996McCoul & Haslam, 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, prior studies have included mixed samples and usually did not control for ethnic differences. Unfortunately, fewer studies have examined the relationship between SSS and risky sex among heterosexual youth and especially among those who are female (Gullette & Lyons, 2005;Spitalnick et al, 2007). More importantly, there is a dearth of studies which have examined the relationship between SSS and risky sex using prospective data (Kalichman et al, 1994(Kalichman et al, , 1996McCoul & Haslam, 2001).…”
mentioning
confidence: 99%
“…In addition, SSS as well as STI risk behaviors are thought to increase during the period of adolescence through young adulthood. Although SSS is generally considered a personality trait (DiClemente et al, 2010;Kalichman et al, 1994;Spitalnick et al, 2007), the expression of such behaviors might increase during adolescence when youth have more autonomy. Education is also likely to be another potential confounder given that more highly educated females might have greater control of their lives and subsequently may demonstrate more relational power during sexual encounters .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Otro factor en el que se ha profundizado por su posible efecto en la asunción del riesgo es la búsqueda de sensaciones. Los jóvenes con alto nivel de búsqueda de sensaciones sexuales tienden a implicarse en mayor medida en relaciones sexuales sin protección y su historial de parejas sexuales es más extenso (spitalnick et al, 2007;Teva y Bermúdez, 2011). Estudios como el de Grov, Parsons y Bimbi (2010) encuentran alto nivel de búsque-da de sensaciones sexuales en los no heterosexuales y lo relacionan con el riesgo sexual atribuido a este colectivo.…”
Section: Introductionunclassified
“…In other words, high sensation-seekers are inclined to seek more stimuli or novel experiences in their lives. These studies have concluded that sensation-seeking is a stable personality trait capable of predicting behaviour (Desrichard & Denarie, 2005;Galloway & Lopez, 1999;Gullette & Lyons, 2006;Martin et al, 2002;Spitalnick et al, 2006;Weisskirch & Murphy, 2004b).…”
Section: Sensation-seeking Researchmentioning
confidence: 99%